A Comparative Analysis of Proficiency Scores of University Students in the United Arab Emirates: The Effectiveness of Using a First Language When Teaching a Second Language in a Reading Class - Traish, Amira (2013)
This study, an investigation into the effectiveness of using a learner’s first language (L1) to teach a second language (L2) in reading comprehension classes, focuses on tertiary students in the United Arab Emirates (UAE). The role of the learner’s L1 in facilitating instruction of an L2 has evoked considerable discussion among linguists and language instructors. Many theorists argue that a student’s L1 contributes to a more successful learning environment and facilitates second language acquisition, particularly with respect to socio-psychological factors such as motivation. The UAE has set guidelines for entrance into English-medium programmes mandating that students attain a 500 in the Test of English as a Foreign Language (TOEFL) or an average Band 5 in the International English Language Testing Service (IELTS). Because English has risen to near total hegemony in the linguistic/language realm, both students and instructors feel pressure to pass these reading examinations; one-third of the country’s tertiary budget is for first-year students. Because of the importance placed on proficiency scores, this study uses empirical data, comparing test scores of two classes and exploring and examining their differences. One instructor uses a student’s L1 (Arabic) to teach reading in L2, and the other does not. Research questions for this study have employed a mixed methods approach (qualitative and quantitative), which has included assessment data from midterm and proficiency exams as well as a student questionnaire, classroom observations, and interviews. The findings of the study, which indicate negligible differences in overall scores, demonstrate that the pedagogical practice has no significant impact on the scores obtained. However, further study is warranted to accommodate more of the variables that may have affected data outcome. It is hoped that this study will prompt additional interest and research in the field of L1/L2 reading instruction and that further exploration of this topic will facilitate improved reading and academic performance for students both in the UAE and elsewhere.